Iron Ores and Iron Oxide Materials 2018
DOI: 10.5772/intechopen.73216
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Removing Direct Blue 15 Dye from Wastewater Using Magnetic Luffa sponge NPs

Abstract: In this study, loaded Luffa sponge membrane forms were modified with ZnO, Fe 3 O 4 , ZnO/ Fe 3 O 4 nanoparticles (NPs) to remove of Direct Blue 15 (DB15), which is a carcinogenic azo dye in aqueous solution. ZnO and Fe 3 O 4 NPs were synthesized using purified peroxidase enzymes from Euphorbia amygdaloides using green synthesis method. Adsorption of DB15 azo dyes was separately studied with membrane forms (LS-pure, LS-ZnO, LS-Fe 3 O 4 , and LS-ZnO/Fe 3 O 4). Optimum contact time, optimum pH, optimum temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…T h e ∆ H ° and ∆S° of the adsorption systems were obtained from the slope and intercept of the plot of 𝑙𝑛 𝐾 𝑑 against 1 𝑇 13. The positive enthalpy (∆H°) of all the adsorbents further confirmed that the adsorption is an endothermic process [26]. The positive values of entropy (∆S°) of all the adsorbents showed increased randomness at the solid-solution interface during the adsorption [27] and also signify an increase in the degree of freedom of the adsorbed species, thus favouring adsorption of Indigo dye.…”
Section: Effect Of Temperaturesupporting
confidence: 52%
See 1 more Smart Citation
“…T h e ∆ H ° and ∆S° of the adsorption systems were obtained from the slope and intercept of the plot of 𝑙𝑛 𝐾 𝑑 against 1 𝑇 13. The positive enthalpy (∆H°) of all the adsorbents further confirmed that the adsorption is an endothermic process [26]. The positive values of entropy (∆S°) of all the adsorbents showed increased randomness at the solid-solution interface during the adsorption [27] and also signify an increase in the degree of freedom of the adsorbed species, thus favouring adsorption of Indigo dye.…”
Section: Effect Of Temperaturesupporting
confidence: 52%
“…The numerical value of ∆𝐺 decrease slightly with increase in temperature, implying that the reaction may be slightly spontaneous and favourable at higher temperature. It also showed an increasing tendency in the feasibility and spontaneity of Indigo dye adsorption [26].…”
Section: Effect Of Temperaturementioning
confidence: 84%